Striatal cue-reactivity and neurotransmitter function in gambling disorder - Bellmunt-Gil, Albert; Majuri, Joonas; Nummenmaa, Lauri; Helin, Semi; Forsback, Sarita; Rajander, Johan; Kaasinen, Valtteri; Joutsa, Juho (AKADEMIAI KIADO ZRT, 2025)
Background:
Abnormal striatal cue reactivity is one of the neurobiological hallmarks of substance use disorders (SUDs). Cue reactivity is associated with relapse, prompting efforts to target its underlying mechanisms with therapeutic interventions. However, the neural correlates of cue reactivity in behavioral addictions, such as gambling disorder (GD), remain poorly understood. Here we investigated striatal cue reactivity and its associations with neurotransmitters in individuals with GD using multimodal neuroimaging.
Methods:
Thirteen subjects with GD and 16 healthy controls (HC) underwent fMRI using a block-design consisting of three different types of visual stimuli: gambling-related, erotic, and neutral videos. The subjects also underwent brain PET imaging with three radiotracers to assess dopamine ([18F]FDOPA), opioid ([11C]carfentanil) and serotonin ([11C]MADAM) function.
Results:
GD subjects showed a significantly greater BOLD response in the dorsal striatum compared to HC when viewing gambling-related versus neutral videos (pFWE< 0.001).
Conclusions:
GD is characterized by increased gambling cue-induced activity in the dorsal striatum, which is linked to mu-opioid receptor availability. The findings highlight the potential role of the mu-opioid system in mediating cue-reactivity in behavioral addictions.